A study of the improvement of foam material sealing technology for wetsuits - Heekyoung Oh; Kyung Wha Oh; Soonjee Park (Fashion and Textiles, 2019)
Abstract The purpose of this study is to propose the most suitable sewing method to produce wetsuits using neoprene fabric. To construct a sewing method sample using neoprene fabric, the samples were prepared using two thicknesses (1.5 t and 3 t) of neoprene fabric. Sewing techniques comprised 10 different methods. The respective seam strengths (KSK 0530) and water resistance (KSK ISO 811) of each sample were measured. The results from the tests conducted using 10 sewing methods revealed that the seam strength of 466.7 N was the highest in the prototype constructed using zigzag and flatlock stitches on 1.5 t. The other samples had seam strengths of approximately 400 N, except for that sewn with straight stitch (113.3 N). For 3 t, the sample sewn using zigzag and flatlock stitches with seam sealing (653.3 N) had the highest strength, and the remaining samples had seam strengths of approximately 630 N, except the sample sewn with straight stitch (164.6 N). Significant factors affecting the seam strength were fabric thickness and the sewing method. Meanwhile, glue and blind stitch with seam sealing had the highest value for water resistance: 414.4 mH2O for 1.5 t and 987.6 mH2O for 3 t. The lowest values were revealed in samples sewn with zigzag and flatlock stitch 14.4 mH2O for 1.5 t and overlock stitch 13.3 mH2O for 3 t. Significant factors affecting water resistance were whether seam sealing was attached and the sewing method used. The expected result of this study, which tests the properties of two neoprene fabric thicknesses with 10 sewing methods, is the suggestion of the most appropriate sewing method for use in the production of a wet suit.